Therapeutic Assessment of High-Intensity Focused Ultrasound for Vulvar Lichen Sclerosus by Active Dynamic Thermal Imaging and Hyperspectral Imaging—A Preliminary Study - Qu, Yingjie; Meng, Yuquan; Feng, Sui; Liu, Maoyu; Xiao, Linlin; Zhang, Xiaoyuan; Zheng, Jinjin; Chang, Shufang; Xu, Ronald X. (Frontiers in Physics, 2020)
Vulvar lichen sclerosus (VLS) is a common inflammatory condition associated with an increased risk of developing vulvar carcinoma. Recently, high-intensity focused ultrasound (HIFU) has been identified as a promising treatment modality for VLS in several clinical trials. However, in HIFU therapy, therapeutic outcome is routinely assessed visually by an expert using standardized grading criteria. Furthermore, such a therapeutic assessment cannot be made until at least 3 months after treatment. Therefore, an objective and timely method capable of quantitatively evaluating HIFU treatment effectiveness is desired, which may help identify patients whose treatment is insufficient promptly and prevent delay in re-treatment. The purpose of this study is to investigate the feasibility of using active dynamic thermal imaging (ADT) and hyperspectral imaging (HSI) as two individual objective and non-invasive optical methods for prompt quantitative assessment of the therapeutic response to HIFU treatment in VLS. From December 2018 to March 2019, 20 female VLS patients who underwent HIFU treatment were evaluated using both the ADT and HSI methods. The effective damage rate from the ADT method and the entropy of feature index from the HSI method were used to develop a multivariate linear discriminant classification model for grading the effectiveness of HIFU treatment in comparison with clinical evaluation gold standard. It was found that ADT was able to correctly differentiate ineffective treatments from effective ones with a sensitivity of 100% and specificity of 100%, while the sensitivity and specificity of HSI were 75 and 87.5%, respectively. The classification results demonstrate the clinical potential of the ADT and HSI methods for timely non-invasive and quantitative assessment of HIFU treatment for VLS.